Are plyometric push-ups a reliable power assessment tool? - Hogarth, L. W.; Deakin, G.; Sinclair, W. (Journal of Australian Strength and Conditioning, 2013)
Upper body power output is a key aspect of athletic ability and sporting performance. As a consequence, empirical-based research has aimed to identify the most effective and efficient ways to develop muscular power. However, identifying the effectiveness of an acute training stimulus or long-term training regime in developing muscular power requires accurate and valid measures of muscular power itself. Furthermore, tests of upper body power output may prove beneficial for talent identification and fatigue monitoring purposes. Therefore identifying reliable and valid means of assessing upper body power output is essential to both the research and coaching community.